In the Footsteps of Kierkegaard - Szewczyk-Haake, Katarzyna,Krysztofiak-Kaszynska, Maria (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2022)
The book is a comparative study of the works of Józef Wittlin and Pär Lagerkvist, in their youth recognized as prominent expressionist writers, and in their later years making the ethical topic the core of their works. In search for ways of expressing ethical dilemmas, the works of Søren Kierkegaard and his concept of indirect communication turned out to be an extraordinarily powerful tool for both writers, enabling them to explore the matters of ethics and morals in a way substantially different from traditional didactic literature. In the reading of Wittlin?s and Lagerkvist?s works undertaken in this book, the perspectives of comparative studies and the history of literature complement and make it possible to describe an important, but rarely recognized phenomenon of modern European literature: its ethical variant
9783631830161
Keywords: Wittlin; Józef; Lagerkvist; Pär; Kierkegaard; Søren; Kierkegaard; Søren - 1813-1855; Lagerkvist; Pär - 1891-1974; Wittlin; Józef - 1896-1976; Expressionism in literature; Ethics in literature; Expressionnisme dans la littérature; Morale dans la littérature; Influence (Literary; artistic; etc.); Criticism; interpretation; etc